PELATIHAN PENANAMAN BIOREEFTEK KEPADA PENGELOLA DESTINASI PANTAI NGURBLOAT, DESA NGILNGOF, KAB. MALUKU TENGGARA - Melissa Justin Renjaan; Pradina Anjarwaty Sukirno; Jamaludin Kabalmay; Safinah Yulianty Sitania; Elisa Charisma Balubun; Karmena Teniwut (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
The development of Ngurbloat Beach is currently progressing rapidly, particularly in terms of infrastructure improvement, the addition of tourist attractions and facilities, as well as the growth of local business actors who continue to enhance the quality of goods and services offered. As a nature-based tourism destination, long-term management is essential to ensure sustainability. However, this condition contrasts with the efforts of Ngurbloat’s management to promote diving and snorkeling tourism in the waters of Ngilngof Village. Coral reef planting activities have never been carried out due to the limited availability of information regarding the condition of the coral reef ecosystem in Ngilngof Village. Therefore, it is necessary to implement coral reef ecosystem management efforts for Ngurbloat Beach managers. The objective of this activity is to train destination managers to develop a conservation-oriented mindset and to understand the procedures for constructing bioreeftek as a method of coral reef conservation. The methods employed in this activity include discussion and training sessions. The results indicate an increased level of empowerment in terms of knowledge and skills among the managers, as they are now capable of constructing bioreeftek independently.Keywords: Ngurbloat, Destination, Bioreeftek